Sweating in Public: Some Thoughts About Writing on the Internet While Being a Woman - Wunker, Erin (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This paper uses autho-theory and affect to think through the repercussions of writing from a gendered perspective in public spaces and on social media.